BIOM-51. ELUCIDATION OF THE TRANSCRIPTOMIC CONSEQUENCES OF KLF4 AND TRAF7 MUTATIONS IN SECRETORY MENINGIOMAS. (14th November 2022) - Michaelsen, Signe Regner; Cloos, Paul; Broholm, Helle; Johansen, Jens; Ahmadov, Ulvi; Mathiesen, Tiit; Kristensen, Lasse; Kristensen, Bjarne Winther; Hansen, Klaus
Abstract: Secretory meningioma (SM) is a benign histological meningioma subtype frequently located in the central skull-base, complicating surgical removal, highlighting the need of gentle targeting treatment alternatives. SM tumors arise from the arachnoid layer in the meninges and are associated with a hotspot p.K409Q mutation in KLF4 combined with different mutations in TRAF7. The objective of this study was to identify how KLF4 and TRAF7 mutations alter signaling in SM tumors.The study includes 16 FFPE samples from SM tumors and three arachnoid cysts as normal-tissue reference. All tissues were histologically confirmed, followed by genomic sequencing of KLF4, TRAF7, NF2 and TERT -promoter (C220T/C228T) using a customized NGS panel. Gene expression profiles were analyzed using NanoString Pan-cancer Progression and Pan-cancer Pathways panels, which resulted in measurement of 1, 202 unique transcripts over background level.All 16 SM tumors presented the KLF4p.K409Q mutation, of which 12 had mutation in TRAF7 (four being p.N520S), while no cysts had mutations in these genes. Neither tumors nor cysts had NF2 or TERT-promoter mutations. PCA analysis showed different RNA expression profiles for SM tumors and cysts, while TRAF7 mutation was without influence on the overall gene expression patterns in the tumors. Sub-analysis found increased KLF4 expression in TRAF7-mutated SM tumors versus non-mutated tumors and cysts at the RNA level, while TRAF7 expression was stable in all samples. In total 98 genes were found differentially expressed (54 up- and 44 downregulated) with a log2-fold change over 1 and an adjusted p-value under 0.05 in tumors versus cysts. Further analyses are planned to explore and validate these results. In conclusion, we find that the KLF4p.K409Q mutation correlates more strongly with SM histology, than the TRAF7 mutation, and that SM tumors have gene expressions profiles that are distinct from normal arachnoid tissue for a number of disease relevant genes.